UHPLC–MS-MS Determination of THC, CBD and Their Metabolites in Whole Blood of Light Cannabis Smokers. Issue 9 (10th October 2022) - Lo Faro, Alfredo Fabrizio; Tini, Anastasio; Gottardi, Josué; Pichini, Simona; Carlier, Jeremy; Giorgetti, Raffaele; Busardò, Francesco Paolo
Abstract: "Light cannabis" is a product legally sold in Europe with Δ 9 -tetrahydrocannabinol (THC) concentration <0.2% and variable cannabidiol (CBD) content. In this study, we aimed to assess the time courses of THC and metabolites (11-nor-9-carboxy-THC and 11-hydroxy-THC) and CBD and metabolites (CBD-7-oic acid, 7-hydroxy-CBD, 6α-hydroxy-CBD and 6β-hydroxy-CBD) in whole blood of 10 healthy participants after smoking one or four light cannabis cigarettes (0.16% THC and 5.8% CBD). Blood samples were collected 0.5–4 h after administration. Blood analysis was performed by reversed-phase ultra-performance liquid chromatography–tandem mass spectrometry in multiple reaction monitoring mode after glucuronide hydrolysis and liquid–liquid extraction in basic and acidic conditions. The method was validated following the most recent guidelines in toxicology: the method was linear, accurate, precise and sensitive (lower limits of quantification ranged from 0.005 to 0.01 ng/mL); carryover, matrix effect, recovery, process efficiency and dilution integrity were also assessed. As previously reported, the main metabolites of THC were THC-COOH and then 11-OH-THC, and the main metabolites of CBD were 7-OH-CBD and then 7-COOH-CBD. The time of the first collection, which likely occurred after the maximal concentration of most of the analytes, and the short monitoring time, up to 4 h after smoking, limited the evaluation of the pharmacokinetic parameters.